ROS production by mitochondria: function or dysfunction? - Palma, Flavio R.; Gantner, Benjamin N.; Sakiyama, Marcelo J.; Kayzuka, Cezar; Shukla, Sanjeev; Lacchini, Riccardo; Cunniff, Brian; Bonini, Marcelo G. (Oncogene, 2024)
In eukaryotic cells, ATP generation is generally viewed as the primary function of mitochondria under normoxic conditions. Reactive oxygen species (ROS), in contrast, are regarded as the by-products of respiration, and are widely associated with dysfunction and disease. Important signaling functions have been demonstrated for mitochondrial ROS in recent years. Still, their chemical reactivity and capacity to elicit oxidative damage have reinforced the idea that ROS are the products of dysfunctional mitochondria that accumulate during disease. Several studies support a different model, however, by showing that: (1) limited oxygen availability results in mitochondria prioritizing ROS production over ATP, (2) ROS is an essential adaptive mitochondrial signal triggered by various important stressors, and (3) while mitochondria-independent ATP production can be easily engaged by most cells, there is no known replacement for ROS-driven redox signaling. Based on these observations and other evidence reviewed here, we highlight the role of ROS production as a major mitochondrial function involved in cellular adaptation and stress resistance. As such, we propose a rekindled view of ROS production as a primary mitochondrial function as essential to life as ATP production itself.